Effects of low-intensity pulsed focal ultrasound-mediated delivery of endothelial progenitor-derived exosomes in tMCAo stroke - Alptekin, Ahmet; Khan, Mohammad B.; Parvin, Mahrima; Chowdhury, Hasanul; Kashif, Sawaiz; Selina, Fowzia A.; Bushra, Anika; Kelleher, Justin; Ghosh, Santu; Williams, Dylan; Blumling, Emily; Ara, Roxan; et al. (Frontiers in Neurology, 2025)
IntroductionExosomes from different sources have been used for therapeutic purposes to target stroke and other disorders. However, exosomes from endothelial progenitor cells (EPCs) have not been tested in any stroke model, and in vivo bio-distribution study is lacking. Targeted delivery of IV-administered exosomes has been a significant challenge. Delivery of exosomes to the brain is a daunting task, and a blood–brain barrier (BBB)-penetrable peptide is being considered. However, the next step in practical treatment will be delivering naïve (unmodified) exosomes to the stroke site without destroying host tissues or disrupting BBB, or the membranes of the delivery vehicles. Low-intensity-pulsed focused ultrasound (LIPFUS) is approved for clinical use in the musculoskeletal, transcranial brain, and physiotherapy clinics. The objectives of the proposed studies were to determine whether LIPFUS-mediated increased delivery of EPC-derived exosomes enhances stroke recovery and functional improvement in mice with transient middle cerebral artery occlusion (tMCAo) stroke.MethodsTo enhance exosome delivery to the stroke area, we utilized LIPFUS. We evaluated stroke volume using MRI at different time points and conducted behavioral studies parallel to MRI to determine recovery. Ultimately, we studied brain tissue using immunohistochemistry to assess the extent of stroke and tissue regeneration.Results and DiscussionIn vivo, imaging showed a higher accumulation of EPC exosomes following LIPFUS without any damage to the underlying brain tissues, increased leakage of albumin, or accumulation of CD45+ cells. Groups of mice (14–16 months old) were treated with Vehicle (PBS), LIPFUS only, EPC-exosomes only, and LIPFUS+EPC-exosomes. LIPFUS + EPC exosomes groups showed a significantly decreased stroke volume on day 7, decreased FluoroJade+ cells, and significantly higher numbers of neovascularization in and around the stroke areas compared to that of other groups.